2004
DOI: 10.1242/dev.01057
|View full text |Cite
|
Sign up to set email alerts
|

Cell movements controlled by the Notch signalling cascade during foregut development inDrosophila

Abstract: Notch signalling is an evolutionarily conserved cell interaction mechanism,the role of which in controlling cell fate choices has been studied extensively. Recent studies in both vertebrates and invertebrates revealed additional functions of Notch in proliferation and apoptotic events. We provide evidence for an essential role of the Notch signalling pathway during morphogenetic cell movements required for the formation of the foregut-associated proventriculus organ in the Drosophila embryo. We demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 41 publications
(44 reference statements)
2
29
0
Order By: Relevance
“…Several signal transduction pathways, including those of Hh, Wg, Decapentaplegic (Dpp), N, and Janus kinasesignal transducer and activator of transcription (JAK-STAT), are required for this epithelial cell sheet movement. [32][33][34] In this study, we identified a multipotent stem cell pool at the F/M junction in adult Drosophila. These cells differentiated into gastric and stomach cells.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Several signal transduction pathways, including those of Hh, Wg, Decapentaplegic (Dpp), N, and Janus kinasesignal transducer and activator of transcription (JAK-STAT), are required for this epithelial cell sheet movement. [32][33][34] In this study, we identified a multipotent stem cell pool at the F/M junction in adult Drosophila. These cells differentiated into gastric and stomach cells.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Accordingly, the range of its reported phenotypes is wide, and Shot plays structural roles and/or mediates signalling events in these contexts. Reported shot mutant phenotypes comprise structural and adhesion defects in the epidermis (Prokop et al, 1998;Röper and Brown, 2003), developmental aberrations of foregut and tracheal tubes (Fuss et al, 2004;Lee et al, 2003), and failed association of microtubules with the fusome during oogenesis (Röper and Brown, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In line with previously published data regarding BTV replication in Culicoides (26), we observed clear infection of fat bodies, salivary glands, and the foregut-midgut junction (proventriculus). BTV-1/NS3mCherry replication in the proventriculus was restricted to ectodermal cells (foregut origin), while the endodermal cells (midgut origin) were uninfected (27,42). These data imply that BTV can enter from the basement membrane (e.g., membrane directly in contact with the hemocoel) of foregut cells but not midgut cells.…”
Section: Discussionmentioning
confidence: 89%